Between Utopia and Reality – The Kurdish Issue in Syria - Hadzhiev, Boyan (Research Papers, 2018)
The aim of this paper is to apply a system approach for the Kurdish issue analysis in Syria (by May 2018). The Middle East is in a period of destabilization after the Arab Spring. Negative effects get their most serious manifestation in Syria, where the country is ripped off by "civil" war, geopolitical clashes and state failure. In this situation, the Syrian Kurds were able to establish their quasi-state structure – the Democratic Federation of Northern Syria. This political subject is considered as a subsystem with inherent centrifugal and centripetal forces. Additionally, two "acceptable" scenarios are outlined for the development of the Kurdish issue. The conclusion is that the Kurds need serious external support, internal consolidation and compromise in order to get the chance to implement their own project for self-government in the new system realities.
Keywords: Syrian conflict; Rojava; Kurdish independence; Scenarios